2019
DOI: 10.48550/arxiv.1906.06711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting p-hacking

Abstract: We analyze what can be learned from tests for p-hacking based on distributions of t-statistics and p-values across multiple studies. We analytically characterize restrictions on these distributions that conform with the absence of p-hacking. This forms a testable null hypothesis and suggests statistical tests for p-hacking. We extend our results to phacking when there is also publication bias, and also consider what types of distributions arise under the alternative hypothesis that researchers engage in p-hack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, we also show results based on de-rounded data. 18 In an earlier version of this paper (Elliott, Kudrin, and Wüthrich (2020)), we showed that de-rounding restores the non-increasingness but not the continuity of the p-curve. The right panel of Figure 4 shows the impact of derounding on the shape of the p-curve.…”
Section: P-hacking Across Different Disciplinesmentioning
confidence: 91%
“…Therefore, we also show results based on de-rounded data. 18 In an earlier version of this paper (Elliott, Kudrin, and Wüthrich (2020)), we showed that de-rounding restores the non-increasingness but not the continuity of the p-curve. The right panel of Figure 4 shows the impact of derounding on the shape of the p-curve.…”
Section: P-hacking Across Different Disciplinesmentioning
confidence: 91%